Three-Year Outcomes Associated With Embolic Protection in Saphenous Vein Graft Intervention: Results in 49 325 Senior Patients in the Medicare-Linked National Cardiovascular Data Registry CathPCI Registry. (March 2015) - Brennan, J. Matthew; Al-Hejily, Wesam; Dai, David; Shaw, Richard E.; Trilesskaya, Marina; Rao, Sunil V.; Brilakis, Emmanouil S.; Anstrom, Kevin J.; Messenger, John C.; Peterson, Eric D.; Douglas, Pamela S.; Sketch, Michael H.
Abstract : Background—: Information is limited on contemporary use and outcomes of embolic protection devices (EPDs) in saphenous vein graft interventions. Methods and Results—: We formed a longitudinal cohort (2005–2009; n=49 325) by linking National Cardiovascular Data Registry CathPCI Registry to Medicare claims to examine the association between EPD use and both procedural and long-term outcomes among seniors (65+ years), adjusting for clinical factors using propensity and instrumental variable methodologies. Prespecified high-risk subgroups included acute coronary syndrome and de novo or graft body lesions. EPDs were used in 21.2% of saphenous vein grafts (median age, 75; 23% women) and were more common in acute coronary syndrome (versus non–acute coronary syndrome; 22% versus 19%), de novo (versus restenotic; 22% versus 14%), and graft body lesions (versus aortic and distal anastomosis; 24% versus 20% versus 8%, respectively). EPDs were associated with a slightly higher incidence of procedural complications, including no reflow (3.9% versus 2.8%; P <0.001), vessel dissection (1.3% versus 1.1%; P =0.05), perforation (0.7% versus 0.4%; P =0.001), and periprocedural myocardial infarction (2.8% versus 1.8%; P <0.001). By 3 years, death, myocardial infarction, and repeat revascularization occurred in 25%, 15%, and 30% of cases, respectively. EPD use was associated with a similar adjusted risk of death (propensity score–matched hazard ratio, 0.96; 95% confidence interval, 0.91–1.02), myocardial infarction (propensity score–matched hazard ratio, 1.00; 95% confidence interval, 0.93–1.09), and repeat revascularization (propensity score–matched hazard ratio, 1.02; 95% confidence interval, 0.96–1.08) in the overall cohort and high-risk subgroups. Conclusions—: In this contemporary cohort, EPDs were used more commonly among patients with high-risk clinical indications, yet there was no evidence of improved acute- or long-term outcomes. Further prospective studies are needed to support routine EPD use. Abstract : Supplemental Digital Content is available in the text.